QTL discovery for resistance to black spot and cercospora leaf spot, and defoliation in two interconnected F1 bi-parental tetraploid garden rose populations - Lau, Jeekin; Gill, Haramrit; Taniguti, Cristiane H.; Young, Ellen L.; Klein, Patricia E.; Byrne, David H.; Riera-Lizarazu, Oscar (Frontiers in Plant Science, 2023)
Garden roses are an economically important horticultural crop worldwide and two major fungal pathogens, black spot of rose (Diplocarpon rosae F.A. Wolf) and cercospora leaf spot of rose (Rosisphaerella rosicola Pass.) affect both the health and ornamental value of the plant. Most black spot disease resistance work has focused on diploid germplasm and little work has been done on cercospora leaf spot resistance. Using newly developed software tools for autopolyploid genetics, two interconnected tetraploid garden rose F1 populations (phenotyped over the course of 3 years) were used for quantitative trait loci (QTL) analysis of black spot and cercospora leaf spot resistance, as well as plant defoliation. QTL for black spot resistance were mapped to LGs 1-6. QTL for cercospora resistance and susceptibility were found in LGs 1, 4, and 5, and for defoliation in LGs 1, 3, and 5. The major locus on LG 5 for black spot resistance coincides with the previously discovered Rdr4 locus inherited from Rosa L. ‘Radbrite’ (Brite EyesTM) the common parent used in these mapping populations. This work is the first report of any QTL for cercospora resistance/susceptibility in tetraploid rose germplasm and the first report of defoliation QTL in roses. A major QTL for cercospora susceptibility coincides with the black spot resistance QTL on LG 5 (Rdr4). A major cercospora resistance QTL was found on LG 1. These populations provide a genetic resource that will further the knowledge base of rose genetics as more traits are studied. Studying more traits from these populations will allow for stacking of various QTL for desirable traits.